The Influence Of Education Based On Self-Efficacy Theory On Interdyalitic Weight Gain (IDWG) In The Hemodialysa Unit - Lily Putri Marito (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Poor fluid management among hemodialysis patients can lead to detrimental outcomes such as high Interdialytic Weight Gain (IDWG), contributing to increased cardiovascular morbidity and mortality. While conventional education on fluid restriction exists in hospitals, non-compliance remains prevalent, highlighting the need for educational approaches grounded in self-efficacy theory to enhance patients' self-confidence in self-management. This study aimed to assess the impact of educational interventions based on self-efficacy theory on IDWG in hemodialysis patients at Malahayati Islamic Hospital. Using a quantitative quasi-experimental pretest-posttest control group design, the study included a total of 68 participants selected through purposive sampling. Statistical analysis revealed a significant difference (p < 0.05) in IDWG scores between the intervention and control groups post-intervention, indicating the effectiveness of self-efficacy-based education in improving compliance with fluid intake restrictions among chronic kidney failure patients undergoing hemodialysis.